Legal Protection for Children in Conflict with the Law Based on Restorative Justice in the Women and Children Service Unit (UPPA) of the Bali Regional Police - Murdana, I Gede; Ketut Wiratny, Ni; Darma Saputra, Komang Edy Darma Saputra (Pelopor Publikasi Akademika, 2025)
The Constitution of the Republic of Indonesia, in Article 18B(2) of the 1945 Constitution, mandates that